Instytucja kuratora spadku nieobjętego, jego prawa i obowiązki w polskim systemie prawa cywilnego - Mazurek, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
One of the few institutions of inheritance law, which so far has not been widely elaborated in the literature on the subject, is the institution of the curator of an inheritance not included. The institution of the curator of the inheritance dates back to Roman law and to this day in its assumptions fulfills the same role that we find on this subject in the literature of ancient Roman lawyers. Judicial practice does not fully use the institution of a probation officer. The article is to bring this institution closer.
Keywords: curator; decrease; heirs